Innovative AE and NDT Techniques for On-Site Measurement of Concrete and Masonry Structures State-of-the-Art Report of the RILEM Technical Committee 239-MCM - Ohtsu, Masayasu; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2016)
This volume, in which on-site measurements of concrete and masonry structures by NDT techniques are comprehensively summarized, focuses on the visualization procedure of the results measured. The research and its outcomes presented in this book treat applications of NDT techniques to on-site measurements. These on-site measurements have been marginally successful as each technique requires a particular analysis. In this regard, visualization and imaging of results are in great demand for practitioners and engineers for inspection. The book will therefore be of great value to the field.    .
Preface -- Introduction, by M. Ohtsu.-Concrete Structures, by C. Grosse, D. Aggelis and T. Shiotani -- Masonry Structures, by G. Lacidogna, F. Accornero, A. Carpinteri -- Computerized AE Tomography, by Y. Kobayashi and T. Shiotani -- Acoustic Emission Analysis for NDE, by D. Aggelis -- Cross-Sectional Visualization of Defects, by SIBIE  T. Watanabe, N. Alver and M. Ohtsu -- 3D-Visualization of Crack Kinematics by AE-SiGMA, by K. Ohno and M. Ohtsu -- Hybrid NDE for Rebar Corrosion in Concrete, by Y. Kawasaki and M. Ohtsu -- On-Site Damage Evaluation by AE and CT in Concrete, by T. Suzuki and M. Ohtsu -- Overview of Visualized NDE for On-Site Measurement, by M. Ohtsu.   .
Keywords: Building materials; Mechanics, Applied; Building Materials; Structural Materials; Engineering Mechanics